DISIPLIN KERJA DAN FASILITAS KANTOR DALAM MEMPENGARUHI KINERJA PEGAWAI - Mahardhika, Mustafidah; Arintowati, Dyan (Universitas Nusantara PGRI Kediri, 2021)
One of the organizational resources that has an important role in achieving its goals is human resources. Human beings as a resource must be able to complete organizational tasks effectively, efficiently, and productively. The effective, efficient, and productive completion of these organizational tasks depends on employee performance. The purpose of this research is to find out the influence of work discipline and office facilities on employee performance in Rejoso District of Nganjuk Regency. This research belong to quantitative research. Data collection techniques by conducting interviews, documentation, and questionnaires. For data analysis using multiple linear regression analysis. The research had several results based on data analysis using multiple linear regression analysis. The results of this study refer to the hypothesis that has been formulated. The first results showed that work discipline partially affected employee performance. The second result showed that office facilities partially affected employee performance. The third result shows that work discipline and office facilities affected employee performance simultaneously.